Reflection and recovery from psychosis during the time of COVID-19 : adaptation in psychotherapy in the United States - Lysaker, Paul H., (Colegio Oficial de Psicólogos de Madrid, 2020)
In response to the coronavirus (COVID-19) pandemic several adaptations have allowed us to continue to provide one form of recovery-oriented psychotherapy to persons with psychosis: Metacognitive Insight and Reflection Therapy (MERIT). These successful adaptations have included the incorporation of patients experience of the pandemic and the exploration of challenges from temporary changes in therapy platforms to deepen reflections about patients self-experience, their experience of intersubjectivity and their own agentic responses to psychosocial challenges.